Cytotoxic Activity of Red Fruit (Pandanus conoideus Lam.) Oil and Its Effect On Cyclooxygenase-2 Gene Expression in Raji Cells - Tih, Fen (Maranatha Christian University, 2016)
The number of cancer patient is increasing, while a really effective therapy has not yet been discovered. One concept of carcinogenesis is the relation between chronic inflammation and cancer. Cyclooxygenase-2 (COX-2) has a carcinogenic effect in inflamed and malignant tissues. Red Fruit contains carotenoid that can suppress COX-2 gene expression and tocopherol, which is a potent inhibitor of COX-2. The purpose of this study is to determine cytotoxic activity of Red Fruit oil and its effect on COX-2 gene expression. The experiment used 5 dosages of Red Fruit, 100, 200, 300, 400, and 500 µg/mL, exposed to Raji cells. However, unexposed Raji cells were used as control. Cytotoxic activities were evaluated by MTT Assay, while Lethal Concentration50 (LC50) was determined through regression-correlation analysis. Red Fruit oil effect on COX-2 gene expression was evaluated by Reversed Transcriptase Chain Reaction (RT-PCR) method and electrophoresis. Electrophoresis bands were analyzed by Scion Image for Windows. Optical Integrated Density (OID) of unexposed and exposed groups were statistically analyzed with one way Analysis of Variance (ANOVA), followed by Duncan test with α=0.05. The results showed that Red Fruit had a cytotoxic activity on Raji cells with LC50 of331.42 µg/mL. Red Fruit suppressed COX-2 gene expression with an effective dosage obtained at 500 µg/mL. Keywords: red fruit, cytotoxicity, cox-2 gene expression, raji cells